American Roundtable: Women in Forensic Science. Issue 1 (7th June 2016) - Wolf, Jody; Jackson, Linda; Ballou, Sue; Houck, Max M.; Smith, Ruth; Funk, Christine; Newman, Reta; Samples, Marie; Siegel, Jay A.
Abstract: As a regular feature, Forensic Science Policy & Management convenes roundtables of forensic professionals to discuss topics related to the profession, its practice, and its management. This roundtable took place at the 2015 American Academy of Forensic Sciences meeting in Orlando, Florida. The focus of this roundtable was to hear from women in forensic science, as they make up the majority of the discipline and the profession. This roundtable, made up of leaders in the field, touches on issues common across the profession as well as those specific to women in a growing STEM field.